Behavioral approach to economy - an explanation of market inefficiencies with emphasis on financial market - Zelić, Mara; Lukavac, Marko (Oeconomica Jadertina, 2018)
The market irregularities that could not be explained by standard economy instigated the scientists to question the rationality and efficiency of the market. The research of economics in the direction of cognitive psychology created a multidisciplinary approach and a new direction in the economics called Behavioral Economics. The Behavioral Economics observes the market participants as irrational beings whose economic decisions are influenced by numerous heuristics and biases. Still, as critics of the traditional approach believe that the behavior and preferences of market participants are not always rational, so critics of Behavioral Economics claim that people are not so average and irrational in making decisions. Independently, the purpose of Behavioral theory is not to remove the neoclassical standard economic theory, but to improve the same theory. As a compromise between behavioral and traditional approach, a new theory of adaptive markets developed, so-called AMH - Adaptive Markets Hypothesis. According to the same, it is not true that market efficiency is either perfect or inexistent, but quite dependent on context.
Keywords: Behavioral Economics; traditional approach; market inefficiency; Behavioral Finance; AMH - Adaptive Markets Hypothesis